The Brauer-Hasse-Noether Theorem in Historical Perspective - Roquette, Peter (Schriften der Mathematisch-Naturwissenschaftliche Klasse, 2005)
The Main Theorem: Cyclic Algebras -- The Paper: Dedication to Hensel -- The Local-Global Principle -- From the Local-Global Principle to the Main Theorem -- The Brauer Group and Class Field Theory -- The Team: Noether, Brauer and Hasse -- The American Connection: Albert -- Epilogue: Käte Hey.
Gesehen am 23.07.2015
Keywords: Brauer-Hasse-Noether-Theorem